Method for inhibiting laser self-oscillation and application thereof

By reducing the concentration of activated ions in the laser crystal and suppressing laser self-excitation, the problems of complex operation and high cost in the prior art are solved, and the output of high-energy Q-regulating laser is achieved.

CN119581987APending Publication Date: 2025-03-07CHINA BUILDING MATERIALS ACADEMY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411508480.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The prior art requires additional processing or additional components when suppressing laser self-excitation oscillation. The operation is complex and costly, making it difficult to achieve the output of high-energy Q-regulating lasers.

Method used

By reducing the concentration of activated ions in the laser crystal to a preset threshold, the laser self-excitation oscillation is suppressed, and the composition of the laser working medium is optimized to control the pump end surface gain.

Benefits of technology

It is realized that without additional processing or adding components, the laser self-excitation oscillation is suppressed, the output energy of the Q-regulating laser is increased, and the high-energy pulsed laser output is obtained, and the operation is simple and cost-effective.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005104731250000011
    Figure HDA0005104731250000011
  • Figure HDA0005104731250000012
    Figure HDA0005104731250000012
  • Figure HDA0005104731250000013
    Figure HDA0005104731250000013
Patent Text Reader

Abstract

The invention provides a method for inhibiting laser self-oscillation and application thereof. According to the method, the self-excited oscillation of the laser crystal is inhibited by reducing the concentration of active ions in the laser crystal to a preset threshold value. The technical problem to be solved by the invention is how to suppress laser self-oscillation, improve output energy of Q-switched laser and obtain high-energy Q-switched laser under the condition that devices are not additionally processed or components are not added, so that the high-energy Q-switched laser is beneficial to stable operation of a laser system, is simple and feasible, is low in cost, and is more practical.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of laser technology, and in particular relates to a method for suppressing laser self-oscillation and application thereof. Background Art

[0002] High-energy Q-switched lasers have high peak power (megawatt level) and narrow pulse width (nanosecond level), which have incomparable advantages over continuously operating lasers and are widely used in mass spectrometry, laser radar, laser ranging and other fields. Compared with semiconductor laser (LD) side pumping, the pump beam under LD end-pumping conditions can better match the laser oscillation mode, with a high degree of spatial overlap, which is conducive to improving the laser beam quality and conversion efficiency; at the same time, the end-pumped laser structure is more compact, which is conducive to reducing the volume and weight of the laser. However, since the absorption of end-pumping light by the laser medium decreases exponentially, a very high gain density is formed at the end of the medium, and the self-excited oscillation caused by this greatly limits the output energy of the Q-switched laser. Therefore, suppressing self-excited oscillation and achieving a high Q-switching dynamic-static ratio have become key technologies for obtaining high-energy end-pumped Q-switched lasers.

[0003] Existing literature reports a variety of self-oscillation suppression methods, for example, roughening the laser working material to destroy the side oscillation conditions can suppress self-oscillation; or, cutting off the self-oscillation circuit by coating the non-light-transmitting surface of the laser working material to suppress self-oscillation; or, suppressing by designing a dual-Q-switched experimental resonant cavity, using a single crystal resonant cavity composed of a YVO4 gain medium, undoped YVO4 and KTP crystal to suppress the generation of self-oscillation, and improving the self-oscillation suppression effect by limiting the effective resonant cavity cross-section, etc. However, the above methods all have their own disadvantages, and their common disadvantage is that the above methods all require additional processing of the device or the addition of original devices, which is relatively complicated and costly. Summary of the invention

[0004] The main purpose of the present invention is to provide a method for suppressing laser self-oscillation and its application. The technical problem to be solved is how to suppress laser self-oscillation without performing additional processing on the device or adding components, thereby improving the output energy of the Q-switched laser and obtaining a high-energy Q-switched laser, which is beneficial to the stable operation of the laser system, simple and easy to operate, and low-cost, and thus more suitable for practical use.

[0005] The purpose of the present invention and the technical problem solved are achieved by adopting the following technical solutions: According to a method for suppressing laser self-oscillation proposed by the present invention, the concentration of activated ions in the laser crystal is reduced to a preset threshold value, so that the self-oscillation is suppressed.

[0006] The purpose of the present invention and the solution to its technical problems can be further achieved by adopting the following technical measures.

[0007] Preferably, in the aforementioned method for suppressing laser self-oscillation, the step of determining the threshold value is as follows:

[0008] S21 obtains a number of laser crystals of the same length doped with different concentrations of active ions;

[0009] S22 simulates and tests the light absorption rate of the pump end face of the laser crystal and at different distances from the pump end face;

[0010] S23 tests the Q-switched laser energy output curve and the laser Q-switched dynamic-static ratio curve of the laser crystal to determine the lower and upper limits of the concentration of activated ions.

[0011] Preferably, in the aforementioned method for suppressing laser self-oscillation, the step of determining the length of the laser crystal is as follows:

[0012] S31 obtains a plurality of laser crystals with the same concentration of active ions and different lengths; the concentration of the active ions is between a lower concentration limit and an upper concentration limit;

[0013] S32 simulates and calculates the change of light absorption rate with the length of the laser crystal under the concentration condition of the activation ions according to Beer's law, and determines the lower limit of the length of the laser crystal according to the change of light absorption rate with the length of the laser crystal;

[0014] S33 simulates the Q-switched laser energy output curves of the laser crystals of different lengths under the concentration conditions of the activated ions to determine the upper limit of the length of the laser crystal.

[0015] Preferably, in the aforementioned method for suppressing laser self-oscillation, the laser crystal is a yttrium aluminum garnet crystal, the doped activation ions are neodymium ions, and the atomic percentage concentration of the doped neodymium ions is 0.4-0.8%.

[0016] Preferably, in the aforementioned method for suppressing laser self-oscillation, the atomic percentage concentration of the doped neodymium ions is 0.5-0.7%.

[0017] Preferably, in the aforementioned method for suppressing laser self-oscillation, the atomic percentage concentration of the doped neodymium ions is 0.6%.

[0018] Preferably, in the aforementioned method for suppressing laser self-oscillation, the length of the laser crystal is 30 to 50 mm.

[0019] Preferably, in the aforementioned method for suppressing laser self-oscillation, the length of the laser crystal is 40 mm.

[0020] Preferably, in the aforementioned method for suppressing laser self-oscillation, the length of the laser crystal is 40 mm; and the atomic percentage concentration of the doped neodymium ions is 0.6%.

[0021] The purpose of the present invention and the technical problem solved by the present invention are also achieved by the following technical solutions: According to the present invention, a high-energy Q-switched laser output according to the aforementioned method for suppressing laser self-oscillation is applied in the field of mass spectrometry, laser radar or laser ranging technology.

[0022] By means of the above technical solution, the method for suppressing laser self-oscillation and its application proposed by the present invention have at least the following advantages:

[0023] The method for suppressing laser self-excited oscillation and its application proposed in the present invention overturn the common understanding of those skilled in the art that a crystal with a high concentration of activated ions is generally used as a laser working medium to ensure sufficient absorption of pump light. The present invention takes the opposite approach and optimizes the composition of the laser working medium to reduce the concentration of activated ions in the laser crystal to a set range, thereby reducing the pump end gain of the laser crystal and obtaining effective control of the pump end gain, thereby suppressing self-excited oscillation and ultimately obtaining high-energy pulsed laser output. That is, through the technical solution of the present invention, it can output high-energy Q-switched laser and is simple, easy and low-cost. At the same time, no additional processing of the device or addition of components is required, which is more conducive to the stable operation of the laser system and has strong feasibility in practical applications.

[0024] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the following is a detailed description of the preferred embodiments of the present invention in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 Schematic diagram of an experimental device for end-pumped Q-switched laser in an embodiment of the present invention;

[0026] Figure 2 is the LD pump light absorption rate of the laser working medium at different activation ion doping concentrations in the embodiment of the present invention;

[0027] Figure 3 is the 1064nm Q-switched output energy of the laser working medium in the embodiment of the present invention at different activation ion doping concentrations;

[0028] Figure 4 is the dynamic-static ratio of 1064nm laser Q-switching under different activation ion doping concentrations of the laser working medium in the embodiment of the present invention;

[0029] Figure 5 It is a simulation curve of the absorption of pump light by the laser working medium with a concentration of 0.6% versus the crystal length in the embodiment of the present invention;

[0030] Figure 6It is the Q-switched energy curve of 1064nm output by the laser working medium with a concentration of 0.6% at different lengths in the embodiment of the present invention. DETAILED DESCRIPTION

[0031] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined purpose of the invention, the following, in combination with the accompanying drawings and preferred embodiments, a method for suppressing laser self-oscillation and its application proposed in accordance with the present invention, its specific implementation method, structure, characteristics and effects are described in detail as follows.

[0032] The present invention provides a method for suppressing laser self-oscillation, wherein the concentration of activated ions in a laser crystal is reduced to a preset threshold value, so that the self-oscillation is suppressed.

[0033] End pumping is the injection of pump light from the pump end face of the laser crystal. The light emitted by the pump light source is focused by the optical coupling system and vertically injected into the pump end face of the laser crystal. The laser crystal absorbs the energy of the pump light, realizes ion number inversion, and thus generates laser. Based on the laser generation mechanism, the current laser working medium generally adopts a crystal with a high concentration of activated ions to ensure sufficient absorption of the pump light. The technical solution of the present invention breaks through the above understanding. According to the cause of the formation of self-excited oscillation, based on the proportional relationship between the absorption coefficient of the laser working material to the pump light and the concentration of activated ions, the absorption rate of the pump light by the pump end face of the laser medium is reduced by reducing the doping concentration of activated ions, thereby reducing the gain of the pump end face, and obtaining effective control of the gain of the pump end face, thereby achieving the suppression of self-excited oscillation, and finally obtaining high-energy pulsed laser output.

[0034] Different laser working materials have different characteristics, and the concentrations of their activated ions are not completely the same; the method for suppressing laser self-oscillation proposed in the present invention can be applied to various laser working materials, and the concentration threshold of their activated ions is preferably determined by the following method:

[0035] The first step is to prepare the test sample, that is, to obtain a number of laser crystals of the same length doped with different concentrations of activated ions. In the pump laser, the concentration of activated ions in the laser crystal material can be adjusted by controlling the crystal growth process; specifically, before the crystal grows, the concentration of activated ions in the final crystal is adjusted by accurately adjusting the ratio of the raw material containing activated ions to other raw materials, and the incorporation efficiency and distribution uniformity of activated ions in the crystal are regulated by adjusting the parameters such as the temperature, pressure, and growth rate of the crystal growth. The sample preparation in the present invention can be entrusted to the laser crystal manufacturer to grow the crystal according to customized specifications, and the present invention does not specifically limit this.

[0036] The second step is to simulate and test the light absorption rate of the pump end face of the laser crystal (specifically the end face of the laser crystal close to the pump side) and the positions at different distances from the pump end face, as shown in the attached figure. Figure 2 As shown, in order to understand the absorption performance of a specific laser crystal, it can be used as a reference when formulating subsequent simulation experimental plans; this step is not necessary but optional. If the absorption characteristics of a certain laser crystal are very clear, this step can be omitted.

[0037] The third step is to test the Q-switched laser energy output curve and the laser Q-switched dynamic-static ratio curve of the laser crystal through experiments, as shown in the attached Figure 3 and attached Figure 4 As shown, the lower and upper limits of the concentration of the activated ions are determined. Specifically, according to the Q-switched laser energy output curve of the laser crystal, it can be seen that the development trend of the laser output energy under different concentrations of activated ions varies with the pump current, and the activated ion concentration in which the laser output energy continues to increase with the pump energy is selected as the optimal concentration range to ensure high laser output energy; according to the laser Q-switched dynamic-static ratio curve, it can be seen that the development trend of the laser Q-switched dynamic-static ratio varies with the pump current under different concentrations of activated ions, and the concentration of activated ions corresponding to a relatively high dynamic-static ratio is selected as the optimal concentration range to ensure that the Q laser output energy continues to increase with the pump current; thus, the optimal laser ion concentration threshold can be determined according to the specific laser working material.

[0038] Laser crystals of the same material but different lengths will also show different performances such as laser output energy. In order to better output high-energy Q-switched lasers, the present invention optimizes the length of the laser crystal, wherein the length optimization for laser crystals of different materials may vary greatly; the steps for optimizing the length of the laser crystal in the present invention are as follows:

[0039] The first step is test sample preparation, that is, obtaining a number of laser crystals with different lengths but the same activation ion concentration; the activation ion concentration is required to be between the lower concentration limit and the upper concentration limit; in order to more accurately optimize the length of the laser crystal, the length optimization can be specifically performed for a material with a certain material and a certain activation ion content, that is, obtaining a number of laser crystals with different lengths for this type of laser crystal material.

[0040] The second step is to simulate and calculate the change of the light absorption rate of the laser crystal with the length of the laser crystal according to Beer's law, as shown in the attached figure. Figure 5 As shown, according to the light absorption rates corresponding to different laser crystal lengths, the laser crystal length corresponding to an absorption rate of at least 80% is preferably selected as the lower limit of the length of the laser crystal of this laser crystal material, thereby avoiding the laser crystal failing to fully absorb the pump LD energy due to the laser crystal length being too short, resulting in a waste of pump power.

[0041] The third step is to simulate the Q-switched laser energy output curve corresponding to the laser crystal material under different length conditions, as shown in the attached figure. Figure 6 As shown, the shorter length corresponding to the condition that can provide higher laser energy is preferably selected as the upper limit of the length of the laser crystal to avoid the corresponding increase in scattering loss caused by the increase in the length of the laser crystal. When the increased scattering loss exceeds the gain generated by the extra absorbed pump light, the output laser energy will be reduced, so that the laser crystal can achieve better performance and effect.

[0042] In the technical solution of the present invention, the laser crystal can be any form of laser working material in the prior art, and the above technical solution can be used to optimize the concentration of the activated ions and the length of the laser crystal so that it can better suppress the laser self-oscillation.

[0043] The present invention also proposes an application of a high-energy Q-switched laser output according to the aforementioned method for suppressing laser self-oscillation in the field of mass spectrometry, laser radar or laser ranging technology.

[0044] The present invention will be further described below in conjunction with specific embodiments, but this should not be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by technicians in this field based on the above-mentioned contents of the present invention still fall within the scope of protection of the present invention.

[0045] Unless otherwise specified, the materials, reagents, etc. involved below are all commercially available products well known to those skilled in the art; unless otherwise specified, the methods described are all methods well known in the art. Unless otherwise defined, the technical terms or scientific terms used should have the common meanings understood by ordinary technicians in the field to which the present invention belongs.

[0046] Example 1

[0047] This embodiment specifically illustrates the technical solution of the present invention by building an end-pumped 1064nm Q-switched laser device in a laboratory.

[0048] As attached Figure 1 As shown, the experimental device includes a pump source LD (1), a semiconductor cooling plate TEC (23), a heat sink HS (22), a fan Fan (21), an LD shaping lens 3, a laser crystal LC (4), a polarizer PS (51), a quarter wave plate QW (52), an electro-optic crystal EOC (53) and an output coupling mirror OC (6). The number of vertical array bars of the pump source LD used in this embodiment is 15, the power of a single bar is 200W, the bar spacing is 0.73mm, and the light emitting area of ​​the LD array is: 10.2×10mm 2, approximately square, easy to shape. In the experimental device of this embodiment, the semiconductor refrigeration plate TEC, the heat sink HS and the fan Fan form a temperature control system 2 of the pump source LD, which can realize precise temperature control of the pump source LD. Among them, the semiconductor refrigeration plate TEC transfers the heat generated by the pump source LD when it is working to the heat sink HS, and then the heat absorbed by the heat sink HS is promptly dissipated by the fan Fan. The energy emitted by the pump source LD is shaped by the LD shaping lens 3 and then output to the laser crystal LC. The LD shaping lens 3 includes a first lens F1 (31) and a second lens F2 (32); the first lens F1 and the second lens F2 are both aspherical lenses, and both sides of them are coated with 800nm ​​broadband anti-reflection film to reduce the loss of pump light.

[0049] Neodymium-doped yttrium aluminum garnet crystal has the advantages of high gain, excellent mechanical and thermal properties, and has become one of the most valuable solid laser crystals, and is widely used in scientific research, industry, medicine and other fields. In this embodiment, Nd:YAG crystal is used as the laser working material to specifically illustrate the technical solution of the present invention, which is not a limitation of the technical solution of the present invention.

[0050] In this embodiment, the laser crystal adopts Nd:YAG rod, the pump surface of which is coated with 1064nm high reflection film and 800nm ​​high transmission film, and the other light-transmitting surface is coated with 1064nm anti-reflection film, which can convert the energy provided by the pump source into a highly parallel and monochromatic laser that is coherent in space and time through the optical resonant cavity. The laser output by the laser crystal LC passes through the polarizer PS, the quarter wave plate QW, the electro-optical crystal EOC and the output coupling mirror OC in sequence, and finally outputs 1064nm Q-switched laser. The polarizer PS is a polarization beam splitter, which polarizes the 1064nm light and can reflect the vertically polarized s light and transmit the horizontally polarized p light. The polarizer PS (51) and the 1064nm quarter wave plate QW (52) and the electro-optical crystal EOC (53) constitute a Q-switching component 5, which modulates the Q value of the resonant cavity, thereby generating a pulsed laser output. In this embodiment, the electro-optical crystal EOC uses a commonly used LN crystal with a size of 9mm×9mm×25mm. Both light-passing surfaces are coated with a 1064nm anti-reflection film and work under a quarter-wave pulse voltage drive to meet the needs of Q switching. The output coupling mirror OC and the pump end face of the laser crystal form a laser resonant cavity to achieve 1064nm laser oscillation output.

[0051] This embodiment first simulates the absorption coefficient of the laser working material to the pump light and the activation ion concentration. 3+ The absorption rate of Nd:YAG to LD light at different doping concentrations is shown in the attached figure. Figure 2 As shown, attached Figure 2The horizontal axis is Distance to pump end (distance to the pump end), unit is mm, and the vertical axis is Absorptivity of pump power (absorption rate of pump light), unit is W / mm. When the pump power is 3000W, Nd 3+ When doped with 1.0 at.%, the pump end face absorption rate of the laser crystal is 2400 W / mm, Nd 3+ When the doping is 0.1 at.%, the pump end face absorption rate of the laser crystal drops to 240 W / mm. In order to observe the development law of the curve clearly, the attached Figure 2 Only Nd is shown 3+ The variation trend of the absorption rate of LD light at different positions of the laser crystal from the pump end face of the laser crystal when the doping concentration is 0.1at.%, 0.2at.%, 0.4at.%, 0.6at.%, 0.8at.%, and 1.0at.%; technicians in this field generally increase the Nd 3+ Doping concentration increases the absorption rate of laser crystals, however, Figure 2 As shown, the applicant has found that the absorption rate of the laser crystal pump end face can be effectively reduced by reducing the activation ion concentration, and the absorbed pump light will be converted into the gain of the laser accordingly, that is, the laser medium pump end face gain will decrease with the decrease of the activation ion doping concentration, that is, the reduction of the activation ion doping concentration is conducive to suppressing the laser self-oscillation and can improve the Q-switching dynamic-static ratio.

[0052] In this embodiment, different Nd 3+ The Q-switched output laser characteristics of Nd:YAG with different doping concentrations are simulated and tested, as shown in the attached figure. Figure 3 The figure shows the Q-switched laser energy output curve when the laser crystal length is 40 mm. Figure 3 The horizontal axis is LDCurrent (pump current), unit is A, and the vertical axis is Q-switched 1064nm energy (Q-switched 1064nm energy), unit is mJ. Figure 3 As shown, when the Nd:YAG crystal concentrations are 0.4at.% and 0.6at.%, respectively, the 1064nm pulsed laser output energy continues to increase with the increase of pump energy (i.e., the increase of pump current), and no saturation phenomenon occurs. When the crystal concentration is 0.8at.%, the 1064nm Q-switched laser output energy no longer changes significantly with the increase of pump energy (i.e., the increase of pump current) after reaching a certain level, that is, the 1064nm Q-switched laser output energy shows obvious saturation, and the output laser pulse energy no longer increases after the pump LD current increases to 130A. It can be seen that the concentration of the activated ions in the laser crystal system in this embodiment is preferably not higher than 0.8at.%.

[0053] In this embodiment, different Nd 3+ The dynamic-static ratio characteristics of the laser Q-switching of Nd:YAG with different doping concentrations are simulated and tested, as shown in the attached figure. Figure 4 The figure shows the dynamic-static ratio curve of 1064nm laser Q-switching under different activation ion doping concentrations of the laser working medium in the embodiment of the present invention. Figure 4 The horizontal axis is LD Current (pump current), unit is A, and the vertical axis is Ratio of dynamic to static (dynamic to static ratio), unit is %. Figure 4 As shown in the figure, with the Nd in Nd:YAG 3+ With the increase of doping concentration, the dynamic-static ratio shows a downward trend, especially in Nd:YAG. 3+ When the doping concentration reaches 0.8at.%, the dynamic-static ratio is only 45% at the highest pump current of 160A, which eventually leads to saturation of the output energy. 3+ When the doping concentration is 0.4at.% and 0.6at.%, at this concentration level, the dynamic-static ratio under the highest pump current is 55% and 61% respectively. The relatively high dynamic-static ratio ensures that the output energy of the 1064nm Q-switched laser increases continuously with the increase of the pump current. This verifies the technical solution of the present invention: using Nd 3+ The low-doping concentration Nd:YAG crystal can reduce the pump end gain, effectively suppress the self-excited oscillation, and ensure that it still maintains a high dynamic-to-static ratio under high pump energy, so as to obtain a higher energy 1064nm pulse laser; and under the condition that the output energy is not saturated, increasing the Nd 3+ The doping concentration can make the laser crystal absorb more pump energy, thereby obtaining higher Q-switched laser output energy, such as Nd 3+ When the doping concentration is 0.6 at.%, the output energy of the laser crystal is higher than that of Nd 3+ When the doping concentration is 0.4 at.%, the output energy is higher. 3+ When the doping concentration is 0.6 at.%, the maximum output energy of the Q-switched laser is 64 mJ under the condition of the maximum LD pump current of 160 A (20 Hz), and the corresponding light-to-light conversion efficiency is 15%. The test data of this embodiment can verify that when the laser crystal is a yttrium aluminum garnet crystal and the doped active ions are neodymium ions, the present invention preferably has an atomic percentage concentration of 0.4 to 0.8% of doped neodymium ions; further preferably has an atomic percentage concentration of 0.5 to 0.7% of doped neodymium ions; and further preferably has an atomic percentage concentration of 0.6% of doped neodymium ions.

[0054] Example 2

[0055] The experimental apparatus and laser crystal are the same as those in Example 1.

[0056] In this embodiment, Nd in the laser crystal Nd:YAG 3+ The doping concentration was fixed at 0.6 at.%, and the optimal crystal length of the laser crystal was simulated, calculated and optimized.

[0057] This example first simulates and calculates Nd according to Beer's law 3+ The absorption of pump light by Nd:YAG laser crystal with doping concentration of 0.6 at.% varies with the length of the crystal, such as Figure 5 The figure shows the simulated curve of the absorption of pump light by the laser working medium with a concentration of 0.6% versus the length of the crystal. Figure 5 The horizontal axis is the length of laser crystal (length of laser crystal), unit is mm, and the vertical axis is the absorptivity of pump power (absorption rate of pump light), unit is W / mm. Figure 5 As shown, as the length of the crystal increases, its absorption of the pump light also increases. When the length of the laser crystal is 30, 40 and 50 mm, the calculated light absorption rates are 80%, 90% and 95%, respectively. In order to avoid the laser crystal failing to fully absorb the pump LD energy due to the laser crystal being too short, resulting in a waste of pump power, when the laser crystal is Nd:YAG, the length of the laser crystal should not be too short. The preferred lower limit of the length of the Nd:YAG laser crystal in the present invention is 30 mm.

[0058] This embodiment also verifies the relationship between the length of the laser crystal material and the energy output of the Q-switched laser. Figure 6 For different lengths Nd 3+ The energy curve of 1064nm Q-switched laser output by Nd:YAG crystal with doping concentration of 0.6at.%, attached Figure 6 The horizontal axis is LD Current (pump current), unit is A, and the vertical axis is Q-switched 1064nm energy (Q-switched 1064nm energy), unit is mJ. Figure 6As shown, the output energy is lower when the crystal length is 30mm. This is because the shorter crystal length fails to fully absorb the pump LD energy, resulting in a waste of pump power. Compared with a 40mm long crystal, a 50mm long crystal absorbs the pump light more fully, which means that more pump energy is absorbed, but its output laser energy is not higher than that of a 40mm long Nd:YAG. This is mainly attributed to the increase in crystal length, which will lead to a corresponding increase in scattering loss. When the increased scattering loss exceeds the gain generated by the extra absorbed pump light, the output laser energy will be reduced. It can be verified from the test data of this embodiment that when the laser crystal is a yttrium aluminum garnet crystal and the doped activation ions are neodymium ions, the preferred length of the laser crystal of the present invention is 30 to 50mm; the preferred length of the laser crystal is 40mm.

[0059] The technical features in the claims and / or the specification of the present invention may be combined, and the combination is not limited to the combination obtained by reference in the claims. The technical solution obtained by combining the technical features in the claims and / or the specification is also within the protection scope of the present invention.

[0060] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention still falls within the scope of the technical solution of the present invention.

Claims

1. A method for suppressing laser self-oscillation, characterized in that: The concentration of activated ions in the laser crystal is reduced to a preset threshold so that its self-oscillation is suppressed.

2. The method according to claim 1, characterized in that The steps for determining the threshold are as follows: S21 obtains a number of laser crystals of the same length doped with different concentrations of active ions; S22 simulates and tests the light absorption rate of the pump end face of the laser crystal and at different distances from the pump end face; S23 tests the Q-switched laser energy output curve and the laser Q-switched dynamic-static ratio curve of the laser crystal to determine the lower and upper limits of the concentration of activated ions.

3. The method according to claim 2, characterized in that The steps for determining the length of the laser crystal are as follows: S31 obtains a plurality of laser crystals with the same concentration of active ions and different lengths; the concentration of the active ions is between a lower concentration limit and an upper concentration limit; S32 simulates and calculates the change of light absorption rate with the length of the laser crystal under the concentration condition of the activation ions according to Beer's law, and determines the lower limit of the length of the laser crystal according to the change of light absorption rate with the length of the laser crystal; S33 simulates the Q-switched laser energy output curves of the laser crystals of different lengths under the concentration conditions of the activated ions to determine the upper limit of the length of the laser crystal.

4. The method according to claim 2 or 3, characterized in that: The laser crystal is a yttrium aluminum garnet crystal, the doped active ions are neodymium ions, and the atomic percentage concentration of the doped neodymium ions is 0.4-0.8%.

5. The method according to claim 4, characterized in that The atomic percentage concentration of the doped neodymium ions is 0.5-0.7%.

6. The method according to claim 4, characterized in that The atomic percentage concentration of the doped neodymium ions is 0.6%.

7. The method according to claim 3, characterized in that The length of the laser crystal is 30-50 mm.

8. The method according to claim 7, characterized in that The length of the laser crystal is 40 mm.

9. The method according to claim 4, characterized in that The length of the laser crystal is 40 mm; the atomic percentage concentration of the doped neodymium ions is 0.6%.

10. Application of high-energy Q-switched laser output by the method for suppressing laser self-oscillation according to any one of claims 1 to 9 in the field of mass spectrometry, laser radar or laser ranging technology.